Clinical Significance of Action Research-Based Seamless Care to Improve Imaging Efficiency and Patients’ Cognition, and Alleviate Patient Anxiety [Letter] - Santosa BJ; Suparji S; Nugroho HSW (International Journal of General Medicine, 2023)
Budi Joko Santosa, Suparji Suparji, Heru Santoso Wahito Nugroho Department Health, Poltekkes Kemenkes Surabaya, Surabaya, Jawa Timur, IndonesiaCorrespondence: Suparji Suparji, Department Health, Poltekkes Kemenkes Surabaya, Jl. Pucang Jajar Tengah-56, Surabaya, Indonesia, Email suparjiyozabri@gmail.com